GE_GERICHTE C/26066/2018 vom 20. April 2021 - GE Cour de justice (2021)
ENTRET;DIVORCE;LIQUIDATION REGIME;PARTAGE;DEUXIEME PILIER;INDEMNITE EQUITABLE | CC.125.al3; CC.123; CC.200; CC.125; CC.126.letb; CC.163; CC.165